1992
DOI: 10.1021/jm00080a004
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function studies in a series of carboxyl-terminal octapeptide analogs of anaphylatoxin C5a

Abstract: The synthesis and structure-activity relationships of C-terminal octapeptide analogues of anaphylatoxin C5a have been studied. The introduction of hydrophobic amino acids into the N-acetylated native octapeptide (N-Ac-His-Lys-Asp-Met-Gln-Leu-Gly-Arg-OH) (1) has led to an analogue with 100 times more activity than the native octapeptide in inhibiting the binding of 125I-labeled anaphylatoxin C5a to human neutrophil membrane receptors. The observed apparent binding Ki's for the compounds (8-10) are in the range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 2 publications
2
33
0
Order By: Relevance
“…It is therefore counted among the anaphylatoxins, as well. This implicates the C-terminus as a receptor-interacting structure as confirmed by deletion proteins (Gerard et al, 1979;Wexler et al, 1985;Bohnsack et al, 1991), synthetic C-terminal analogue peptides Kawai et al, 1992;Or et al, 1992;Ember et al, 1992;) and rhC5a mutants (Mollison et al, 1989). In additition to the C-terminal residue Arg74, Lys68 and Leu72 (and apparently aromatic residues in position 67) are also involved in receptor interaction.…”
mentioning
confidence: 86%
“…It is therefore counted among the anaphylatoxins, as well. This implicates the C-terminus as a receptor-interacting structure as confirmed by deletion proteins (Gerard et al, 1979;Wexler et al, 1985;Bohnsack et al, 1991), synthetic C-terminal analogue peptides Kawai et al, 1992;Or et al, 1992;Ember et al, 1992;) and rhC5a mutants (Mollison et al, 1989). In additition to the C-terminal residue Arg74, Lys68 and Leu72 (and apparently aromatic residues in position 67) are also involved in receptor interaction.…”
mentioning
confidence: 86%
“…In support of this claim, mutations in the ligand C-terminal tail inhibit ligand binding and receptor activation (19). Synthetic hexapeptides derived from the tail of C5a can compete with the full-length ligand and serve as full agonists (18,20), indicating that the tail interacts with the receptor. Receptor residues Ile 116 , Arg 206 , and Val 286 have been identified as points of interaction with the C5a C-terminal tail (21,22).…”
Section: G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…In support of this claim, mutations in the ligand C-terminal tail inhibit ligand binding and receptor activation (19). Synthetic hexapeptides derived from the tail of C5a can compete with the full-length ligand and serve as full agonists (18,20) * This work was supported by National Institutes of Health Grant R01 GM63720 (to T. J. B.).…”
mentioning
confidence: 99%
“…Initial analysis showed that the C-terminal arginine of C5a was important for binding affinity and functional activity (Chenoweth & Hugli, 1980;Braunwalder et al, 1992). In addition, a synthetic octapeptide corresponding to the C-terminus of C5a was able to mimic some of the C5a-induced functional responses but with a greatly reduced potency (Kawai et al, 1992). Using a mutant analysis of the full-length protein, 2 groups have identified some of the other amino acids of C5a involved with receptor binding (Mollison et al, , 1991Carney & Hugli, 1993).…”
mentioning
confidence: 99%